Pelatihan Kewirausahaan sebagai Pengembangan Ekonomi Desa Pulau Tayan pada Kelompok Ibu PKK - Febriyani, Diah Febriyani; Ramadhan, Rizani; Amanda, Askia Fitri; Arsita, Riris; Nonong, Veron Nika; Paula, Trillia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Women's empowerment through entrepreneurship is key to achieving broader community welfare. This community service article aims to describe the implementation of the entrepreneurship knowledge and skills development program for mother of the family welfare movement in Tayan Island Village. Through this program, it is expected to increase the capacity of mother of the family welfare movement in creating sustainable creative businesses, thus ultimately contributing to village economic growth and community welfare. The activities carried out include site visits, coordination with the chairperson of mother of the family welfare movement, debriefing for service members, socialization of entrepreneurial strategies, as well as question and answer sessions and experience sharing. The results of the activities showed an increase in participants' motivation and knowledge about entrepreneurship, as well as an understanding of business management strategies and online marketing. This activity is expected to strengthen the role of mother of the family welfare movement in family and community welfare, and advance the local economy in Tayan Island Village.